2020
DOI: 10.1111/nyas.14541
|View full text |Cite
|
Sign up to set email alerts
|

Understanding tolerance to cell wall–active antibiotics

Abstract: Antibiotic tolerance-the ability of bacteria to survive for an extended time in the presence of bactericidal antibiotics-is an understudied contributor to antibiotic treatment failure. Herein, I review the manifestations, mechanisms, and clinical relevance of tolerance to cell wall-active (CWA) antibiotics, one of the most important groups of antibiotics at the forefront of clinical use. I discuss definitions of tolerance and assays for tolerance detection, comprehensively discuss the mechanism of action of β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 290 publications
(642 reference statements)
3
22
0
Order By: Relevance
“…Therefore, A. baumannii strains in stasis, a relevant physiological state during infection when the cell is known to fortify the cell envelope and slow growth/division 22 , are highly tolerant to lethal meropenem concentrations. While these data agree with current dogma that -lactam-dependent killing is strictly proportional with growth rate 7,23,24 , subsequent analysis revealed that stationary phase A. baumannii cells experience significant cell envelope damage upon Fluorescence intensity measurements were equivalent in treated and untreated cells. Furthermore, fluorescence intensity was higher at the midcell, where the divisome regulates daughter cell formation, suggesting the recovered population had resumed division (Fig 1E).…”
Section: Meropenem Susceptible a Baumannii Strains Are Tolerant Form Spheroplasts And Resume Normal Morphology And Growth Upon Removal Ofsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, A. baumannii strains in stasis, a relevant physiological state during infection when the cell is known to fortify the cell envelope and slow growth/division 22 , are highly tolerant to lethal meropenem concentrations. While these data agree with current dogma that -lactam-dependent killing is strictly proportional with growth rate 7,23,24 , subsequent analysis revealed that stationary phase A. baumannii cells experience significant cell envelope damage upon Fluorescence intensity measurements were equivalent in treated and untreated cells. Furthermore, fluorescence intensity was higher at the midcell, where the divisome regulates daughter cell formation, suggesting the recovered population had resumed division (Fig 1E).…”
Section: Meropenem Susceptible a Baumannii Strains Are Tolerant Form Spheroplasts And Resume Normal Morphology And Growth Upon Removal Ofsupporting
confidence: 87%
“…However, antibiotic tolerance, a population's ability to survive otherwise toxic levels of transient antibiotic treatment for extended periods, likely acts as a stepping-stone to true resistance [3][4][5] . Antibiotic tolerance is characterized by survival of cell populations in a non-dividing state, where the minimal inhibitory concentration does not change and cells revert to normal growth when the antibiotic is removed, degraded or diluted [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a well-known regulator of polymyxin resistance, the PhoPQ two-component system was not previously known to respond or mediate tolerance to carbapenem treatment. As tolerance (and spheroplast formation in particular) is a possible culprit for antibiotic treatment failure (2, 3, 43), our results suggest a potential for combination therapies with histidine kinase inhibitors to increase the efficacy of carbapenems.…”
Section: Discussionmentioning
confidence: 79%
“…PBPs are enzymes that synthesize the cell wall, an essential structure composed mainly of the polysaccharide peptidoglycan (PG). In many well-studied model organisms, PBP inhibition induces cell wall degradation and often subsequent lysis through the action of cell-wall degrading enzymes (collectively referred to as “autolysins”) in a poorly-understood manner (2). While lysis is the canonical response of model organisms like Escherichia coli K12, many susceptible clinical isolates of Gram-negative pathogens (including prominent Enterobacterales clinical isolates like Klebsiella spp .…”
Section: Introductionmentioning
confidence: 99%
“…Cell wall is the outermost structure of the plant pathogenic fungi and bacteria, which plays important role in maintaining cell shape and integrity. It also maintains normal metabolism, ion exchange, and osmotic pressure in cells [142]. Some marine compounds can inhibit the formation of microbial cell walls, thus suppress the growth or kill the pathogens.…”
Section: Affect Cell Wall Structuresmentioning
confidence: 99%